2017
DOI: 10.15446/dyna.v84n203.61723
|View full text |Cite
|
Sign up to set email alerts
|

Sugarcane bagasse and its potential use for the textile effluent treatment

Abstract: En Colombia, la caña de azúcar representa el segundo cultivo con mayor extensión. Se estima que a partir de los ingenios azucareros se producen aproximadamente 6 millones de toneladas de bagazo de caña de azúcar, BCA, de los cuales 5 millones son utilizados ineficientemente para la quema de calderas. El BCA está compuesto principalmente por celulosa, hemicelulosa y lignina, posibilitando su uso como un potencial adsorbente. En particular, en esta investigación se evaluó la viabilidad del BCA para la remoción d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 34 publications
0
6
1
Order By: Relevance
“…Farhad Zeinaly et al [25] their obtained results revealed cellulose 44.09%, hemicellulose 23.89% and lignin 21.42%; where cellulose result was closed to our result; also lignin result was slightly lower than our result; but for hemicellulose result it was very low compared to our obtained result. Cueva-Orjuela et al [26] from their work reported that cellulose 59.1%, hemicellulose 24.3% and lignin 6.8%; where our results of cellulose was low compared to their obtain result; also our results of hemicellulose and lignin were high compared to their obtained results; these may be due to environmental issues. In general the results obtained for cellulose, hemicellulose and lignin in this study were found in the range of previous studies.…”
Section: Resultscontrasting
confidence: 66%
“…Farhad Zeinaly et al [25] their obtained results revealed cellulose 44.09%, hemicellulose 23.89% and lignin 21.42%; where cellulose result was closed to our result; also lignin result was slightly lower than our result; but for hemicellulose result it was very low compared to our obtained result. Cueva-Orjuela et al [26] from their work reported that cellulose 59.1%, hemicellulose 24.3% and lignin 6.8%; where our results of cellulose was low compared to their obtain result; also our results of hemicellulose and lignin were high compared to their obtained results; these may be due to environmental issues. In general the results obtained for cellulose, hemicellulose and lignin in this study were found in the range of previous studies.…”
Section: Resultscontrasting
confidence: 66%
“…Sugarcane is one of the most important crops for sugar production around the world. According to the Food and Agriculture Organization located in Rome, Italy (FAO), Colombia is the second-largest producer of sugarcane in South America, with an estimated 220,000 ha planted in 2019 [ 15 ], which produces approximately 6 million tons of bagasse by year [ 16 ]. This agro-industrial by-product is generated in sugar factories after the cane stem has been crushed and pressed.…”
Section: Introductionmentioning
confidence: 99%
“…It produces 80% of all Colombian sugar, and also it counts for 50% of all local agricultural production. This industry produces a lot of agroforestry residues, approximately 6 million tons of sugarcane bagasse a year [15]. The availability and low cost of this residue are thought as competitive advantages for the development of sustainable biocomposites in this region.…”
Section: Introductionmentioning
confidence: 99%